2005
DOI: 10.1021/bi048510j
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Endostatin to Phosphatidylserine-Containing Membranes and Formation of Amyloid-like Fibers

Abstract: Endostatin, the 20-kDa C-terminal NC1 domain of collagen XVIII, is an endogenous inhibitor of tumor angiogenesis and tumor growth. A major problem in reconciling the many reported in vitro effects of endostatin is the lack of a high-affinity receptor, and a search for the latter continues. In accordance with the above, the molecular mechanisms of action of endostatin remain elusive. We show here that endostatin binds to membranes containing acidic phospholipids, phosphatidylserine (PS) or phosphatidylglycerol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 30 publications
3
87
0
Order By: Relevance
“…For example, it is known that an ␣-lactalbumin folding variant with molten globule features is able to kill specifically tumoral cells (35); similarly, apoptin multimers, exposing extensive hydrophobic surfaces (36), kill specifically tumoral cells (37). Endostatin also displays antitumoral specificity upon aggregation triggered by its interaction with membrane phosphatidylserine (38), whereas the 32-kDa ectodomain fragment of CD44 displays selective toxicity to differing cell lines (39). Most pore-forming toxins of bacterial or eukaryotic origin kill target cells by oligomerizing into their plasma membranes, where they produce nonspecific pores (40 -42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is known that an ␣-lactalbumin folding variant with molten globule features is able to kill specifically tumoral cells (35); similarly, apoptin multimers, exposing extensive hydrophobic surfaces (36), kill specifically tumoral cells (37). Endostatin also displays antitumoral specificity upon aggregation triggered by its interaction with membrane phosphatidylserine (38), whereas the 32-kDa ectodomain fragment of CD44 displays selective toxicity to differing cell lines (39). Most pore-forming toxins of bacterial or eukaryotic origin kill target cells by oligomerizing into their plasma membranes, where they produce nonspecific pores (40 -42).…”
Section: Discussionmentioning
confidence: 99%
“…most often hydrophobic) surfaces as well as of a suitable membrane lipid composition in exposed cells. Indeed, it has been repeatedly reported that anionic phospholipids, such as phosphatidylserine, which becomes exposed in the outer membrane leaflet in apoptotic and tumoral cells, are putative docking sites for amyloid aggregates or can favor aggregate formation, thus initiating membrane impairment (38,50,51). Membrane cholesterol modulates membrane fluidity and may affect the incorporation of toxic aggregates into exposed cells (24,52) as well as membrane-associated Abeta fibrillogenesis and toxicity in neuronal cells (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo abnormal partial unfolding or folding may result from destabilization of the protein structure upon mutation, oxidation, heat stress, or changes in pH and the dielectric properties of the protein's local environment (Zerovnik, 2002;Trzesniewska et al, 2004;Gamblin et al, 2000). Evidently, protein-membrane interactions may play an important role in modulating conformational transitions of both membrane and soluble proteins, including amyloidogenic ones (Zhao et al, 2004(Zhao et al, , 2005). An increasing number of studies provides support to the idea that lipid bilayers can lower the activation energy barrier for protein unfolding.…”
Section: Protein Conformational Changesmentioning
confidence: 99%
“…Cell membrane is further thought to be the direct target mediating amyloidinduced cell death. Amyloid formation has been reported to induce membrane permeabilization resulting from alterations in bilayer structure and/or uptake of lipids into the forming fiber (Sparr et al, 2004;Zhao et al, 2004Zhao et al, , 2005Lin et al, 2001;Michikawa et al, 2001). It has also been hypothesized that extraction of membrane lipids by the forming amyloid (Sparr et al, 2004;Zhao et al, 2004) may be the direct cause for membrane permeabilization and cell death (Zhao et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…16,18 As a result, amyloid fibrillogenesis is dramatically accelerated by negatively charged lipids, as has been shown, for example, for Aβ, 19,20 prion, 21 α-synuclein, 22 and IAPP. 18 Formation of amyloid-like fibrils was also induced by negatively charged phospholipids for several other cytotoxic and apoptotic proteins, 17,23 including antimicrobial peptides. 24,25 Amyloid-type fibrils obtained in vitro in the presence of lipid membranes were found to incorporate phospholipids.…”
Section: Introductionmentioning
confidence: 99%